Faith-Based Sense of Community among Volunteers in a Muslim Women’s Organization in Indonesia: A Qualitative Case Study - Situmorang, Nina Zulida; Prameswari, Adinda; Widyowati, Arini (Universitas Ahmad Dahlan, 2025)
This study aimed to explore the experience of a sense of community among volunteers of Yayasan Rumpun Nurani (YRN), a faith-based social organization in Yogyakarta, Indonesia. Using a qualitative case study design, this study examines how shared Islamic values and informal community structures contribute to volunteer cohesion and organizational sustainability. Data were collected through focus group discussions, participatory observation, and document analysis of twenty active volunteers. Data analysis was conducted using Braun and Clarke's six-step thematic analysis approach. The results of the analysis resulted in eight interrelated themes: shared values and vision, belonging, peer support and emotional contagion, flexible commitment, spiritual and personal growth, conflict management, youth engagement and regeneration, and social and professional benefits. These findings suggest that spiritual values, relational dynamics, and non-hierarchical participation play a central role in fostering a sense of community in the context of grassroots communities. Theoretically, this research enriches community psychology by contextualizing the theory of sense of community in collectivist Islamic culture. Practically, the results of this study provide insights for the development of faith-based empowerment programs that strengthen social cohesion, women's participation, and cross-generational involvement in volunteer organizations.